FORMING SPIRITUAL VALUES IN FUTURE TEACHERS BASED ON CREATIVE APPROACHES - Arziev, Shinabat Abdirakhmanovich (SCIENCE and SOCIETY, 2026)
This article analyzes the scientific and theoretical foundations for the formation of spiritual values in future teachers based on creative approaches. It highlights the issues of developing creative competence, improving value-based approaches, and organizing spiritual and educational activities through innovative pedagogical technologies within the educational process. The article also reveals the pedagogical possibilities of forming national and universal human values in students through the heritage of Eastern thinkers and modern interactive teaching methods. It is substantiated that an educational process organized on the basis of creative approaches contributes to the development of spiritual maturity, independent thinking, and professional competence in future teachers.
Keywords: creative approach; spiritual values; future teacher; creative competence; value-based approach; innovative pedagogical technologies; spiritual and educational activities; professional competence; interactive methods; pedagogical education